DESIGN OF CHANNEL WAVEGUIDE â RING RESONATOR COUPLER - Ridho, Muhammad
Optics is a branch of physical science that describes light propagation and its interaction with matter. Optics can be combined with electronics technology, giving birth to a mixed discipline called opto-electronics. Photonics is a part of optics that describes light interaction as particle-like packets of light, which called is photons. One of sub-disciplines of photonics is integrated photonics, which is based on the use of photons instead of electrons. One of the important components in integrated photonic devices is the waveguide, a structure that can confine light and be used for light transmission from one point to another point without losing power. In integrated photonic device analysis, coupling mode theory is used to describe the coupling interaction between two closely spaced waveguides. One of the optical devices that use coupling is the filter system of ring resonator. In this Final Assignment, we described how to calculate the coupling coefficient of a single ring resonator and how to create the transmission characteristics curve of a single ring resonator. From the coupler design studied in this Final Assignment, we obtained the coupling coefficient of the bus waveguide coupled with the single ring resonator system as ???? = ???????????? ? (3.75 × 10?1) ? ???? (1.22 × 10?9) with its modulus |????????????| ? 3.75 × 10?1 . From the transmission characteristics curve, which describes the relation of transmission intensity ????(????) toward phase shift ???? in propagation constant ???? = 5.98 ?????????1 we obtained a very sharp response of FWHM and finesse values of ????? = 0.09 ???????????? and ???? = 67.55 respectively.